Bulk Surveillance Under the Investigatory Powers Act 2016: An Analysis of European Human Rights Law Compliance and Protection - SEAN LOONEY (2023)
Bulk surveillance powers appear to be simultaneously contravening the general principles of European human rights law while being accepted as necessary by the jurisprudence the ECtHR and CJEU. This thesis illustrates this issue by analysing the UK Investigatory Powers Act 2016 as an example. Touted as the example for a modern bulk surveillance apparatus, the IPA instead shows how the human rights protection provided by the ECtHR and CJEU does not adequately protect against the dangers of bulk surveillance. This thesis first provides the legislative history and framework for the IPA before providing an analysis of the bulk surveillance powers described in the IPA, focusing on how they are described in the legislation, how they work in practice and what harms they incur. The takeaways from these analyses are two-fold. First, the harms caused by the use of these bulk powers goes beyond harms to privacy. Bulk powers also impact on freedom of expression and freedom of assembly. Second, each of these bulk powers operates in a qualitatively different way and thus the level of protection provided by safeguarding must be tailored to each individual power. These chapters are complemented by an analysis of the ECtHR’s approach to bulk interception caselaw, and the CJEU’s approach to data retention caselaw. These chapters find that both the ECtHR and CJEU allow for the use of bulk surveillance powers but limit their use through the use of required levels of safeguarding. Given the wide scope of harms caused by these bulk powers these safeguards aren’t sufficient. Returning to the IPA, the thesis presents the case that the authorisation procedures, supervision and review mechanisms contained within the legislation cannot account for the harms caused by the use of these bulk powers while simultaneously being likely to be judged as compatible with the ECHR and EU law. Finally, the thesis proposes possible improvements for the IPA’s legislative framework.